Epithelial-Myoepithelial Carcinoma of the Base of Tongue with Possible Lung Metastases - Michael Y. Chen; Vipul Vyas; Ryan Sommerville (Case Reports in Otolaryngology)
Background. Epithelial-myoepithelial carcinomas are rare neoplasms usually arising from the salivary glands. There is limited evidence in the literature on their prognosis in the base of the tongue but other cases have resolved without recurrence. Methods. The patient underwent biopsies demonstrating the diagnosis of epithelial-myoepithelial carcinoma of the base of tongue and a PET scan showed multiple bilateral rounded pulmonary nodules. Results. The patient declined chemotherapy and radiotherapy to maximise his quality of life and passed away under management from palliative care several months later. Discussion. This is the only case in the literature of this type of carcinoma in the base of the tongue resulting in metastases and a poor prognosis. The case highlights the importance of checking for metastases in such lesions and their potentially serious outcomes if left untreated.